Implementasi Standar Akuntansi Syariah pada Praktik Penyaluran Dana Musyarakah di Indonesia dan Malaysia - Febrianto, M. Nanang; Nur Asiyah, Binti (AKTSAR: Jurnal Akuntansi Syariah, 2025)
Every activity in Islam must not contradict sharia principles, including financial recording that avoids usury, uncertainty, speculation, and increases accountability. This study aims to analyze the implementation of Sharia accounting standards in the practice of musyarakah fund distribution in Indonesia and Malaysia. This study uses a qualitative approach with a literature study referring to national and international indexed journals, OJK, BNM, annual reports, and ebooks related to musyarakah accounting. Data analysis is conducted through identification, selection, and interpretation to obtain research findings. Findings in Indonesia and Malaysia indicate that the regulation of musyarakah distribution and accounting is governed by OJK and SAC-BNM, which refer to IFRS standards. The musyarakah financing scheme in Indonesia is not limited to capital financing (partnership) and asset financing schemes, but also includes refinancing financing, which is broader than in Malaysia. Implementation in the field has not fully implemented musharakah accounting standards and Islamic principles. The inhibiting factors stem from lower Islamic financial literacy, the quality of human resources, and suboptimal musharakah contracts, which necessitate socialization, education, and market segmentation.